Kinerja Dinas Pariwisata Dalam Penyusunan Laporan Akuntabilitas Kinerja Instansi Pemerintah (LAKIP) Kabupaten Minahasa Selatan - Pundy Zaghena; Michael Mamentu; Elfie Mingkid (AGRI-SOSIOEKONOMI, 2022)
This study aims to determine the performance of the Tourism Office in preparing the Government Agency Performance Accountability Report (GAPAR) of South Minahasa Regency. The location of the research implementation is the Tourism Office of South Minahasa Regency. This study uses a descriptive qualitative type, which describes the actual situation of the object that is the research problem, the opinion of the informant about the object and then relates it to the existing phenomena to produce conclusions. Selection of informants using purposive sampling technique and taken as many as 7 people. Data collection techniques in this study are through observation, interviews, documentation. Checking the validity of the data uses triangulation to test the credibility. Data analysis techniques in this study are data reduction, data presentation, and drawing conclusions. The results of the study show that based on performance indicators there are still obstacles in the process of preparing GAPAR at the South Minahasa Regional Secretariat, namely obstacles to coordination and communication/information that are less effective, limited human resources and equipment, no SOP for preparing GAPAR in each section. and there is no support from parties who have the authority to provide rewards and sanctions, if the performance appraisal process has been carried out by taking into account the existing indicators, the implementation will run well without any significant obstacles.